2012
DOI: 10.1590/s1982-56762012000200007
|View full text |Cite
|
Sign up to set email alerts
|

Detection of isometric, dsRNA-containing viral particles in Colletotrichum gloeosporioides isolated from cashew tree

Abstract: Fungi are disease-causing agents in plants and affect crops of economic importance. One control method is to induce resistance in the host by using biological control with hypovirulent phytopathogenic fungi. Here, we report the detection of a mycovirus in a strain of Colletotrichum gloeosporioides causing anthracnose of cashew tree. The strain C. gloeosporioides URM 4903 was isolated from a cashew tree (Anacardium occidentale) in Igarassu, PE, Brazil. After nucleic acid extraction and electrophoresis, the band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Previous results indicate that the virulence of the fungal species may be related to mycovirus infection. Since other studies have reported similar results (Dalzoto et al, 2006;Figueirêdo et al, 2012;Zhong et al, 2014) and taking the behavior into consideration, mycoviruses may be considered a biocontrol tool against pathogen virulence.…”
Section: Rna Interference (Rnai) and Future Applicationsmentioning
confidence: 61%
“…Previous results indicate that the virulence of the fungal species may be related to mycovirus infection. Since other studies have reported similar results (Dalzoto et al, 2006;Figueirêdo et al, 2012;Zhong et al, 2014) and taking the behavior into consideration, mycoviruses may be considered a biocontrol tool against pathogen virulence.…”
Section: Rna Interference (Rnai) and Future Applicationsmentioning
confidence: 61%
“…Literature information shows the existence of interactions among fungus, viruses and host plants (Lamichhane & Venturi, ; Márquez, Redman, Rodriguez, & Roossinck, ; Ghabrial & Suzuki ; Figueiredo et al, ). These interactions may cause physiological and morphological changes in phytopathogens, leading to reduced pigmentation, asexual sporulation, loss of fertility and/or reduced growth rate, as well as reduction in virulence (Kanematsu, Sasaki, Onoue, Oikawa, & Ito, ; Rosseto et al, ; Van de Sande et al, ; Xie & Jiang, ).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested the presence of a novel twosegment dsRNA virus termed Colletotrichum acutatum partitivirus 1. Figueirêdo et al (2012) reported the detection of a mycovirus in a strain of Colletotrichum gloeosporioides causing anthracnose in cashew trees. TEM revealed the presence of isometric particles (30-35 nm in diameter), confirming that the infection of this C. gloeosporioides strain was by a mycovirus.…”
Section: Discussionmentioning
confidence: 99%
“…TEM was used as described by Figueirêdo et al (2012). Briefly, hyphae and spores of fungi grown in PDA medium were carefully removed with a glass slide, transferred to a mortar containing 0.2 mL 0.05 M cacodylate buffer, pH 7.2, and macerated with pestle.…”
Section: Temmentioning
confidence: 99%